Strategi Guru Kelas Dlam Mengatasi Kesulitan Belajar Membaca dan Menulis Siswa SDN 4 Kuranji Tahun Pelajaran 2023/2024 - Kumala Dewi, Nurin; Hakim, Samsul; Sudrajat, Husaen (BALE LITERASI, 2025)
This study aims to identify and analyze the strategies implemented by classroom teachers to address reading and writing difficulties among students at State Elementary School 4 Kuranji for the 2023/2024 academic year. The research method employed is qualitative. Data were collected through observation, interviews, and documentation. The findings indicate that teachers utilize various strategies, including individualized learning approaches, the use of interactive learning media, and intensive tutoring outside of regular class hours. Additionally, parental involvement in the students' learning process is regarded as an important factor in overcoming these learning difficulties. This study contributes to the understanding of the critical role of teachers in supporting students' basic literacy skills and underscores the necessity of collaboration between schools and parents.